THE RELATIONSHIP BETWEEN WORKLOAD PERCEPTION AND JOB SATISFACTION WITH THE ATTACHMENT OF WORK TO MANUFACTURING EMPLOYEES - Fitriatul Masruroh; Andik Matulessy; Amanda Pasca Rini (International Conference on Humanity Education and Society (ICHES), 2023)
This research aims to examine the relationship of perception of workload and job satisfaction with the bonding of work on employees of PT. X Gresik. The proposed hypothesis is there is a link between workload perception and job satisfaction with employee engagement. The population in this research is PT. X who has a position as manager until Asst. Superisor, which has had a working period over 2 years. Samples were taken from the firstline up level of 87 employees. This research technique purposive sampling. The free variables in the study are perceptions of workload and job satisfaction, while the variable is the job attachment that is revealed with the scale of multiple regression analysis with the help of SPSS program version 21 for Windows. The results of the study stated that there was a significant workload in relation with the bonding of work which means that when the perception of workload is getting lower the employee bonding is getting higher. The result of employee satisfaction is very significant with positive with a working bond meaning the higher employee satisfaction, the higher the bonding of work. These results indicate that the hypothesis proposed in this study was received.